The challenge of rebuilding coexistance in Euskadi - Arias Ergueta, Pedro Luis (Razón y fe, 2018)
The reconstruction and revitalization of coexistence in the Basque Country involves relativizing possible alamrmist visions and unattainable assumptions as well as avoiding forgetfulness and the false healing of the wounds caused. It requires and demands abandoning all coverage of ETA's violence, and publicly acknowledging the lack of love and oversight suffered by the victims of ETA terrorism and, no less, for weakening identity drives that, once sacralized, keep us away from reconciliation and forgiveness.